Infusion of Sexuality Education into Junior Secondary School Basic Science and Technology Curriculums for Prevention of Sexual Abuse among Students - Wababi , Popoola Sanusi; Haruna O, Idris (International Journal of Educational Management, 2025)
The study focused on the need for the infusion of sexuality education into Junior Secondary School Basic Science and Technology curriculum for prevention of sexual abuse among students. One hundred BST teachers were used for the study. The instrument named Teachers Opinion on the Infusion of Sexuality Education into Basic Science and Technology Curriculum (TOISEBSTC) was used for the study. Mean statistical analysis was used for the research study. The findings of the study showed that the curriculum of BST has the potential to carry the issue of sexuality education contents for prevention of sexual abuse among students. Teachers' opinions showed that relevant contents of sexuality education exist in the contents of the current BST curriculum hence easy infusion. Based on the research findings, infusion of all inclusive sexuality education contents into BST curriculum will not cause curriculum overload. The BST teachers can teach detailed sexuality education contents in the BST curriculum without bias or reservations. Among the recommendation made was to conduct refresher programmes for teachers on the issue of sexuality education. No doubt, this effort is capable of preventing sexual abuse among students.